2020
DOI: 10.5964/jspp.v8i1.1072
|View full text |Cite
|
Sign up to set email alerts
|

How education did (and did not) accentuate partisan differences during the Ebola outbreak of 2014-15

Abstract: Education exacerbates partisan gaps in scientific knowledge and attitudes. However, previous findings about the extent and symmetry of this moderation have been mixed. As a conceptual replication of previous research, this study examines whether education asymmetrically moderates the Democrat-Republican gap in attitudes about Ebola virus disease (EVD) and policies to combat EVD. Weighted data from a survey of 1,461 non-institutionalized adults drawn from a probability-based panel were collected during the 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Understanding how different ideological groups respond to disease threat is vital for both theoretical and practical reasons. At a theory level, although work evaluating the psychology of disease outbreaks is growing (e.g., Karwowski et al, 2020;Harper et al, 2020;Martin, 2020;Pennycook et al, 2020;Sibley et al, 2020;Zettler et al, 2020), we currently do not have many guiding theories concerning the interface of ideology and disease outbreaks more broadly. Thus, in the present project we aim to use the current data to aid in theory-building in this regard.…”
Section: Why Should Researchers Care? Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Understanding how different ideological groups respond to disease threat is vital for both theoretical and practical reasons. At a theory level, although work evaluating the psychology of disease outbreaks is growing (e.g., Karwowski et al, 2020;Harper et al, 2020;Martin, 2020;Pennycook et al, 2020;Sibley et al, 2020;Zettler et al, 2020), we currently do not have many guiding theories concerning the interface of ideology and disease outbreaks more broadly. Thus, in the present project we aim to use the current data to aid in theory-building in this regard.…”
Section: Why Should Researchers Care? Theoretical and Practical Implicationsmentioning
confidence: 99%
“…The background for the design of the Ebola study is described elsewhere (Painter, DiClemente, & von Fricken, 2017). Although the Ebola study focused on public health, some findings from the Ebola survey have been published in the psychology literature (Martin, 2020).…”
Section: Hexaco Traits Big Five Traits and Covid-19mentioning
confidence: 99%
“…Attitudes pertaining to COVID-19 and health policy were measured using 14 (or 16?) questions, each of which was derived from an Ebola survey (Martin, 2020;Painter et al, 2017). There were two questions each under each of these topics: travel, fear of infection, perceived governmental preparedness, perceived severity of the disease, suspicion toward exposed persons, and interest in vaccines.…”
Section: Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, consider the cultural and social psychology of the worldwide COVID-19 pandemic. Much research and theorizing has suggested that disease outbreaks influence cultural beliefs, with a largely unresolved debate centering around the potential causal influence of disease on ideological conservatism (e.g., Beall et al, 2016;Brenner & Inbar, 2015;Helzer & Pizarro, 2011;Martin, 2020;Oosterhoff et al, 2018;Shook et al, 2017;Tybur et al, 2016) and sometimes conflicting results for COVID-19 research in particular (e.g., Brownstein, 2020;Choma et al, 2021;Karwowski et al, 2020;Zettler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%